Kinetic and phenotypic changes in murine lymphocytes infected with murine gammaherpesvirus-68 in vitro - Dutia, Bernadette M.; Stewart, James P.; Clayton, Robert A. E.; Dyson, Heather; Nash, Anthony A. (Journal of General Virology, 1999)
Primary infection with murine gammaherpesvirus-68 (MHV-68), as with other members of the gammaherpesvirus subfamily, is characterized by a lymphoproliferative phase. MHV-68 causes acute splenomegaly and an infectious mononucleosis-like syndrome in which there is expansion of the CD8+ T cell subset. In long-term infections, MHV-68 is associated with lymphoma development. In order to elucidate the mechanisms underlying the proliferative processes, the events following infection of murine splenocytes or purified murine B lymphocytes in vitro have been examined. MHV-68 infection prolonged the viability of murine splenocytes and stimulated cellular proliferation. Unlike Epstein–Barr virus and herpesvirus saimiri, MHV-68 did not cause growth transformation. Growth transformation did not occur even when cells with a predisposition to transformation were infected or when culture conditions were selected to enhance the viability of the cells. Following MHV-68 infection, the latency-associated viral tRNAs were transcribed. However, transcription of the other known latency- associated gene, M2, was not observed. In addition, there was no evidence of productive virus replication either by staining with antibodies specific for late virus antigens or by in situ hybridization for early and late mRNAs. In contrast to Epstein–Barr virus- and herpesvirus saimiri-infected lymphocytes, where episomal genomes are seen, Gardella gel analysis indicated that the primary lymphocytes infected by MHV-68 in vitro contained only linear virus DNA. This DNA was nuclease sensitive, indicating that, while MHV-68 was efficiently uncoated, its circularization in vitro was extremely inefficient. These results are discussed in terms of the host–virus interaction.